Analisis Pemanfataan Dana Desa dalam Pemberdayaan Masyarakat dan Pembangunan Berkelanjutan - Nada Wima Putri; Aldri Frinaldi (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine the results of the use of village funds in Lewalu village related to community empowerment and sustainable development and whether the use of village funds is in accordance with the plan or not. This research was carried out using a qualitative descriptive approach in which data collection was based on the factors that became the main supporters of the research object. In this study, the withdrawal of informants was based on a purposive sampling technique which was based on the main criteria, namely that they must be the people of Lewalu Village, regardless of their role or position in the village. Thus data collection is done by means of interviews, observation and documentation. Data analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. Then the validity of this data was tested by triangulation of sources which was then analyzed. The use of village funds in community empowerment and sustainable development found the research results, namely; the use of village funds in Lewalu Village related to community empowerment and sustainable development has been carried out by the village government in accordance with the stages of village financial management as stated in the Minister of Home Affairs Regulation No. 20 of 2018. Utilization of village funds in Lewalu Village provides many benefits for the community. . With the existence of village funds in Lewalu Village, it has provided improvements in Lewalu Village such as increasing physical buildings and infrastructure and increasing community productivity through empowerment programs that have been carried out.